Conversations with myself - Mandela, Nelson, 1918-2013.; Kani, John.; James, Peter Francis (New York : Macmillan Audio, 2010)
Rising from political prisoner to the presidency of post-apartheid South Africa, Nelson Mandela is often a subject of inspiration. Here, with decades of preparation, Mandela offers insight on his long imprisonment, his years as president, and beyond. Part biography, part philosophy, Conversations with myself gives listeners an opportunity to delve into the mind and soul of one of history's most endearing leaders.
Unabridged.
Compact discs.
Includes South African choral music from the Soweto region and bonus archival interviews with Nelson Mandela by Richard Stengel & Ahmed Kathrada.
Read by John Kani ; foreword and introduction read by Peter Francis James.
Keywords: Mandela, Nelson, -- 1918-2013.; Presidents -- South Africa -- Biography; Political prisoners -- South Africa -- Biography; Apartheid -- South Africa; South Africa -- Politics and government -- 20th century; Audiobooks